Cellulose-based artificial SEI (solid electrolyte interface) film as well as preparation method and application thereof
By preparing cellulose-based artificial SEI film on the surface of the negative electrode of the lithium battery, the problems of lithium dendrites growth and electrolyte consumption of the negative electrode of the lithium battery are solved, the circulation and low-temperature performance of the lithium battery are improved, and the number of lithium ion migrations is achieved. and mechanical properties.
Patent Information
- Application Number
- CN202411198445.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-20
AI Technical Summary
There are uncontrolled lithium dendrites growth problems during the peeling and deposition cycle of lithium battery negative electrodes, resulting in continuous electrolyte consumption, decreased Coulomb efficiency and shortened battery life. The existing technology cannot effectively improve the low-temperature performance and cycling performance of the battery.
Using the preparation method of cellulose-based artificial SEI film, cellulose nanofibers are gelled hydrochloride and chemically grafted 2-bromoisobutyryl bromide and 2,3,5,6-tetrafluoro-4-hydroxybenzene Sodium sulfonate forms single-ion polymer TF-HBSC, which increases the number of lithium ions migration and conductivity and slows down the decomposition rate of electrolyte.
It significantly improves the circulation and low-temperature performance of lithium batteries, enhances uniform dispersion of lithium ions, extends battery life, and increases capacity at low temperatures. The cellulose-based artificial SEI film has high mechanical properties and excellent ionic conductivity.
Smart Images

Figure CN119171003A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a cellulose-based artificial SEI membrane and a preparation method and application thereof. Background Art
[0002] The negative electrode of lithium batteries has the problem of uncontrolled lithium dendrite growth during the stripping and deposition cycles due to the highly active nature of lithium. Studies on lithium negative electrodes have shown that the solid electrolyte interface (SEI) plays a vital role in the stability and cyclability of lithium battery negative electrodes. However, the inhomogeneity of the naturally formed SEI can lead to uneven migration and deposition of lithium ions on the surface of lithium battery negative electrodes. At the same time, the poor mechanical properties and easy breakage of the naturally formed SEI make it unable to withstand the huge volume expansion of the lithium battery negative electrode. In addition, the inefficient lithium ion diffusion pathway and low lithium ion transfer number (t Li+ ) will lead to severe concentration polarization inside the lithium battery, resulting in depletion of lithium ion supply during deposition. As a result, lithium dendrites will form and continue to grow, leading to continuous consumption of electrolyte, rapid decay of Coulomb efficiency and shortened lithium battery life.
[0003] The current power batteries mainly use a small amount of film-forming additives to introduce into the electrolyte to solve the defects of the natural SEI film. The role of the film-forming additive is to promote the formation of a stable and effective SEI film on the surface of the electrode material. Among them, the reduction potential of the electrochemical reduction type additive is higher than that of the organic solvent, and it can preferentially undergo electrochemical reduction on the electrode surface to form an ideal SEI film. Including vinylene carbonate, acrylic nitrile, SO2, CS2 and polysulfides. The existing technology cannot slow down the continuous consumption of the electrolyte, and it is also unable to effectively improve the low temperature performance of the battery. The continuous consumption of the electrolyte will lead to a continuous decrease in the capacity and coulomb efficiency of the lithium battery, and eventually the battery will be scrapped due to insufficient internal active lithium ions (the capacity drops to 80%).
[0004] Therefore, it is necessary to develop a cellulose-based artificial SEI membrane with high mechanical properties, high lithium ion migration number and excellent ionic conductivity and its preparation method to slow down the decomposition rate of the electrolyte and improve the cycle performance and low-temperature performance of lithium batteries. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the above-mentioned background technology, to provide a cellulose-based artificial SEI membrane with high mechanical properties, high lithium ion migration number and excellent ionic conductivity and a preparation method thereof, to slow down the decomposition rate of the electrolyte, and to improve the cycle performance and low-temperature performance of the lithium battery.
[0006] The technical solution of the present invention is: a method for preparing a cellulose-based artificial SEI film, comprising:
[0007] First, cellulose nanofiber CNF is gelated with hydrochloric acid to obtain CNF gel; then 2-bromoisobutyryl bromide BiBB is chemically grafted onto the CNF gel to obtain the precursor CNF-Br; then 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate sodium TF-HDBSNa is chemically grafted onto the precursor CNF-Br, and the resulting crude product is dialyzed to convert the sodium ions on the crude product into lithium ions to obtain a single-ion polymer TF-HBSC; finally, the single-ion polymer TF-HBSC is formed into a film to obtain a cellulose-based artificial SEI membrane.
[0008] The above scheme grafted the fluorine-rich 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonic acid small molecules onto cellulose nanofibers (CNF) through surface-initiated atom transfer radical polymerization to prepare a single-ion polymer (TF-HBSC), and then made an artificial SEI film on the surface of the negative electrode of the lithium battery. The fixed sulfonate anions on TF-HBSC increased the number of lithium ion migration, thereby promoting the uniform dispersion of lithium ions and slowing down the decomposition rate of the electrolyte. At the same time, the strong dissociation ability of F atoms increases the capacity of the battery at low temperatures, ultimately improving the cycle performance and low-temperature performance of the lithium battery.
[0009] In the present invention, the synthesis route of CNF-Br is shown in the following formula (1):
[0010]
[0011] In the present invention, the synthesis route of TF-HBSC is shown in the following formula (2).
[0012]
[0013] In the above formulas (1) and (2), n is an integer of 1,000 to 10,000.
[0014] Preferably, the preparation of CNF gel comprises: placing cellulose nanofiber CNF in water to form a CNF dispersion with a concentration of 1.0-2.0wt%, adding hydrochloric acid at room temperature for gelation reaction for 2-8h, the amount of hydrochloric acid used being 0.008-0.01mmol HCl per 1g CNF, to obtain CNF gel.
[0015] Preferably, the preparation of the precursor CNF-Br includes: dispersing CNF gel in a solvent DMF, slowly dropping a DMF solution containing triethylamine and 2-bromoisobutyryl bromide under the protection of argon and an ice bath environment, stirring at room temperature for 12 to 24 hours to cause a grafting reaction, and separating, washing, and drying after the reaction is completed to obtain the precursor CNF-Br.
[0016] Furthermore, the molar ratio of the precursor CNF-Br: 2-bromoisobutyryl bromide: triethylamine is 1:2-2.4:0.6-0.8. Furthermore, the molar ratio of the precursor CNF-Br: 2-bromoisobutyryl bromide: triethylamine is 1:2.4:0.7.
[0017] Furthermore, in the preparation process of the precursor CNF-Br, separation is specifically as follows: pouring the reaction solution into a large amount of 50% by volume ethanol aqueous solution to precipitate the product and obtain a slightly yellow precipitate; washing is specifically as follows: repeatedly washing with 50% by volume ethanol aqueous solution; drying is freeze-drying to obtain a solid product precursor CNF-Br.
[0018] Preferably, the TF-HBSC preparation comprises:
[0019] Under argon protection, CNF-Br, sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate and potassium carbonate were placed in a solvent DMSO and stirred at 120-180°C for 12-24 hours for grafting reaction. After the reaction was completed, a crude product was obtained by separation and washing. The crude product was dialyzed to convert sodium ions into lithium ions, and TF-HBSC was obtained after freeze-drying.
[0020] Furthermore, the molar ratio of CNF-Br: sodium hydroxybenzenesulfonate: potassium carbonate is 1: 0.5-0.6: 1-1.5. Furthermore, the molar ratio of CNF-Br: sodium hydroxybenzenesulfonate: potassium carbonate is 1: 0.5: 1.25.
[0021] Furthermore, during the preparation of TF-HBSC, separation is specifically performed by pouring the reaction solution into a large amount of 50% by volume ethanol aqueous solution to precipitate the product to obtain a white colloidal precipitate; and washing is specifically performed by repeatedly washing with 50% by volume ethanol aqueous solution.
[0022] Preferably, the dialysis treatment comprises: placing the crude product in a dialysis bag and sealing it, then immersing the dialysis bag in a lithium chloride aqueous solution with a concentration of 1 to 1.5 mol / L to convert sodium ions into lithium ions, the immersion time is 24 to 36 hours, and taking out and freeze-drying after immersion to obtain TF-HBSC.
[0023] Preferably, the monoionic polymer TF-HBSC film formation includes: placing TF-HBSC in a solvent DMSO and stirring at room temperature for 6 to 12 hours to obtain a TF-HBSC dispersion, dripping the TF-HBSC dispersion onto the substrate surface under an argon environment, and heating at 60 to 90°C for 4 to 12 hours to remove the solvent to obtain a transparent cellulose-based artificial SEI film. Further, the concentration range of the TF-HBSC dispersion is 6 to 10 mg / mL. Further, heating at 80°C for 8 hours to remove the solvent to obtain a transparent cellulose-based artificial SEI film.
[0024] Preferably, the method for preparing the cellulose-based artificial SEI film comprises:
[0025] S1. placing cellulose nanofiber CNF in water to form a CNF dispersion with a concentration of 1.0-2.0 wt%, adding hydrochloric acid at room temperature for gelation reaction for 2-8 h, with the amount of hydrochloric acid being 0.008-0.01 mmol per 1 g CNF, to obtain CNF gel;
[0026] S2, dispersing CNF gel in solvent DMF, slowly dropping a DMF solution containing triethylamine and 2-bromoisobutyryl bromide under the protection of argon and ice bath environment, stirring at room temperature for 12 to 24 hours to cause grafting reaction, separating, washing and drying after the reaction is completed to obtain the precursor CNF-Br;
[0027] S3. Under argon protection, CNF-Br, sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate and potassium carbonate are placed in a solvent DMSO, and stirred at 120-180° C. for 12-24 hours to cause a grafting reaction. After the reaction is completed, a crude product is obtained by separation and washing. The crude product is dialyzed to convert sodium ions into lithium ions, and TF-HBSC is obtained after freeze-drying;
[0028] S4. Place TF-HBSC in solvent DMSO and stir at room temperature for 12 to 24 hours to obtain a TF-HBSC dispersion. Drop the TF-HBSC dispersion onto the substrate surface under an argon environment, heat at 60 to 90° C. for 4 to 12 hours to remove the solvent and obtain a transparent cellulose-based artificial SEI film.
[0029] Furthermore, the preparation method of the cellulose-based artificial SEI film includes:
[0030] S1. Cellulose nanofibers CNF are placed in water to form a CNF dispersion with a concentration of 2.0 wt%, and hydrochloric acid is added at room temperature for gelation reaction for 2 h, with the amount of hydrochloric acid being 0.008 mmol per 1 g CNF to obtain CNF gel;
[0031] S2, dispersing CNF gel in solvent DMF, slowly dropping a DMF solution containing triethylamine and 2-bromoisobutyryl bromide under the protection of argon and ice bath environment, stirring at room temperature for 24 hours to cause grafting reaction, separating, washing and drying after the reaction is completed to obtain precursor CNF-Br;
[0032] S3. Under argon protection, CNF-Br, sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate and potassium carbonate were placed in a solvent DMSO and stirred at 180°C for 24 hours to undergo a grafting reaction. After the reaction was completed, a crude product was obtained by separation and washing. The crude product was dialyzed to convert sodium ions into lithium ions, and TF-HBSC was obtained after freeze-drying.
[0033] S4. Place TF-HBSC in solvent DMSO and stir at room temperature for 12 hours to obtain a TF-HBSC dispersion. Drop the TF-HBSC dispersion onto the substrate surface under an argon environment, and heat at 80°C for 8 hours to remove the solvent to obtain a transparent cellulose-based artificial SEI film.
[0034] The present invention also provides a cellulose-based artificial SEI membrane, which is prepared by the above cellulose-based artificial SEI membrane preparation method, wherein the TF-HBSC structural formula is as follows, and n is an integer of 1000 to 10000.
[0035]
[0036] The present invention also provides an application of a cellulose-based artificial SEI film for a negative electrode of a lithium battery.
[0037] The beneficial effects of the present invention are:
[0038] 1. In the process of preparing TF-HBSC of the present invention, the purpose of first grafting 2-bromoisobutyryl bromide BiBB is to convert the hydroxyl group on the polymer main chain into a halogen to facilitate the next step of grafting reaction, and the role of triethylamine in the grafting process is to provide an alkaline reaction environment; the purpose of grafting sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate is to be grafted onto the polymer main chain, wherein the F atom provides the ability to dissociate lithium ions and thus improve the battery performance at low temperatures, and the sulfonic acid group provides a single ion transmission channel. The role of potassium carbonate in the grafting process is to provide alkaline reaction conditions, and at the same time react with the HBr generated by the reaction to promote the forward reaction and increase the degree of reaction.
[0039] 2. The sulfonate anions on TF-HBSC increase the lithium ion migration number, thereby promoting the uniform dispersion of lithium ions and slowing down the decomposition rate of the electrolyte. The strong dissociation ability of F atoms increases the capacity of the battery at low temperatures and improves the cycle performance and low-temperature performance of the lithium battery.
[0040] 3. The cellulose-based artificial SEI membrane prepared by the present invention has good mechanical properties, with a tensile strength of up to 20.3 MPa and an elongation of up to 10.8%. This is mainly because the sulfonic acid groups and F atoms of 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonic acid are introduced into the hydroxyl-rich CNF polymer skeleton to act as proton acceptors, and a large number of hydroxyl groups on the CNF polymer act as proton donors, which in turn leads to the formation of strong hydrogen bond interactions between a large number of hydroxyl groups and sulfonic acid groups and F atoms.
[0041] 4. The ionic conductivity of the cellulose-based artificial SEI membrane prepared in the present invention is as high as 4.87×10 -4 S cm -1 , ionic conductivity at 85℃ is as high as 3.12×10 -3 S cm -1 , which is about 3 times that of the existing PP film; when the applied voltage is 10mV, the lithium ion migration number of TF-HBSC is 0.64, which is about twice that of the pure lithium negative electrode lithium ion migration number, and the lithium ion migration performance is excellent.
[0042] 5. The initial discharge capacity of the negative electrode made of the cellulose-based artificial SEI membrane prepared in the present invention is 89.1 mAhg at -20°C -1 After 1079 stable cycles, the discharge capacity is as high as 92.1 mAh g -1 The capacity is 103.37% of the initial capacity (higher than 100% mainly due to self-heating and interface stability after several cycles), and it has excellent cycle stability and reversibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is the infrared characterization image of TF-HBSC prepared in the present invention.
[0044] Figure 2 (a) is the cross-sectional SEM image of the TF-HBSC@Li negative electrode, and (b) is the S element mapping image of the surface SEM image of the TF-HBSC@Li negative electrode.
[0045] Figure 3 (a) is the TEM image of TF-HBSC membrane, (b) is the TEM image of pure CNF membrane, (c) is the AFM image of TF-HBSC membrane, and (d) is the 3D surface reconstruction image of TF-HBSC membrane.
[0046] Figure 4 (a) shows the stress-strain curves of CNF and TF-HBSC films, and (b) shows the contact angles of commercial electrolyte (1M LiPF6 / EC / DMC) on TF-HBSC films and PP films.
[0047] Figure 5(a) is the electrochemical window test diagram of TF-HBSC, and (b) is the ionic conductivity test diagram.
[0048] Figure 6 This is a test diagram of lithium ion migration number (from left to right: TF-HBSC@Li negative electrode, HBSC@Li negative electrode, pure lithium negative electrode).
[0049] Figure 7 (a) shows the long-term cycle performance of Li||LiFePO4 battery at 10C and 25°C, and (b) shows the long-term cycle performance at 1C and -20°C.
[0050] Figure 8 (a) is the SEM surface of pure lithium anode, (b and e) are the SEM surface and cross-sectional images of pure lithium anode after square wave cycling, (c and f) are the SEM surface and cross-sectional images of TF-HBSC@Li anode after square wave cycling, and (d) is the SEM surface image of the original TF-HBSC@Li anode.
[0051] Fig. 9 (a) is the rate performance of the Li||LiFePO4 battery assembled with the TF-HBSC@Li negative electrode, HBSC@Li negative electrode and pure lithium negative electrode at 0.1C to 10C. (b) is the charge and discharge curves of the Li||LiFePO4 battery assembled with the TF-HBSC@Li negative electrode at different rates from 0.1 to 10C.
[0052] Fig.10 (a) shows the electrochemical performance of Li||LiFePO4 batteries TF-HBSC@Li anode, HBSC@Li anode, and pure Li anode (a) long-term cycling performance at 10C and 25℃ and (b) long-term cycling performance at 1C and -20℃. DETAILED DESCRIPTION
[0053] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The drugs used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods in the art unless otherwise specified.
[0054] This embodiment provides a method for preparing a cellulose-based artificial SEI film, the steps are as follows:
[0055] S1. Preparation of CNF gel
[0056] Cellulose nanofibers CNF were placed in water to form a CNF dispersion with a concentration of 2.0 wt% (volume 62.5 mL), and 1 mL of 0.01 mol / L hydrochloric acid was added at room temperature for gelation reaction for 2 h to exchange the sodium ions in CNF with hydrogen ions to obtain CNF gel;
[0057] S2. Preparation of CNF-Br
[0058] Disperse CNF gel (5 mmol) in 20 mL of N,N-dimethylformamide (DMF) solvent. Under the protection of argon and ice bath environment, dissolve triethylamine (3.5 mmol) and 2-bromoisobutyryl bromide (12 mmol) in 40 mL of DMF. Slowly drop the DMF solution containing triethylamine and 2-bromoisobutyryl bromide. Stir at room temperature for 24 hours to cause grafting reaction. After the reaction is completed, pour into a large amount of 50% by volume ethanol aqueous solution to precipitate the product to obtain a slightly yellow precipitate. Then, wash repeatedly with 50% by volume ethanol aqueous solution, and freeze-dry to obtain the precursor CNF-Br with a yield of about 86%.
[0059] S3. Under argon protection, CNF-Br (2 mmol), sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate (1 mmol), and potassium carbonate (2.5 mmol) were placed in a solvent of dimethyl sulfoxide (DMSO), and stirred at 180°C for 24 hours to cause a grafting reaction. After the reaction was completed, a large amount of 50% by volume ethanol aqueous solution was poured into the solution to precipitate the product, and the product was allowed to stand for a period of time to obtain a white colloidal precipitate. The product was then repeatedly washed with a 50% by volume ethanol aqueous solution to obtain a crude product. The crude product was placed in a dialysis bag and sealed. The dialysis bag was immersed in a 1 mol / L lithium chloride aqueous solution for 24 hours to convert the sodium ions in the crude product into lithium ions. The dialyzed product was then freeze-dried for 24 hours to obtain the final product with a yield of 84%, named TF-HBSC.
[0060] S4. Place 30 mg of TF-HBSC in 5 mL of DMSO solvent, and then continue stirring at 25 ° C for 12 hours to obtain a slightly whitish uniform emulsion. Subsequently, use a pipette to take 50 μL of the above solution and drop it on the surface of a circular lithium sheet with a diameter of 16 mm in a glove box filled with argon (H2O < 0.01 ppm, O2 < 0.01 ppm). Heat the lithium sheet with the solution added at 80 ° C for 8 hours. Finally, TF-HBSC will form a transparent film with an average thickness of about 5 μm on the surface of the lithium sheet. The lithium sheet with the TF-HBSC artificial SEI film formed is named TF-HBSC@Li negative electrode.
[0061] At the same time, a transparent membrane with a thickness of about 25 μm was prepared on a glass plate using TF-HBSC using the same steps for tensile testing, electrochemical testing, and a series of physical and chemical tests.
[0062] Comparative Example
[0063] This comparative example provides a HBSC without a fluorine group. The preparation method is basically the same as that of the embodiment, except that sodium 4-hydroxybenzenesulfonate is used to replace sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate in step S3. The remaining steps remain unchanged and the same grafting synthesis operation is performed to obtain a final product marked as HBSC.
[0064] Similarly, HBSC without fluorine groups was used to prepare artificial SEI film-modified lithium sheet HBSC@Li negative electrode and separator HBSC according to the same step S4 as the above TF-HBSC for comparison experiment.
[0065] Performance Testing
[0066] 1. Chemical structure characterization
[0067] like Figure 1 The infrared spectrum of TF-HBSC prepared by the present invention is shown in FIG. 1478 cm -1 The corresponding peak is the stretching vibration peak of the S=O group on the sulfonate group, 1365 cm -1 The corresponding peak is the stretching vibration peak of the CF group on the benzene ring, 863 cm -1 The corresponding peak is the stretching vibration peak of the CH group on the benzene ring, 1730 cm -1 The corresponding peak is the stretching vibration peak of the -COO group on the precursor CNF. The results of infrared spectroscopy show that the small molecule sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate has been successfully grafted onto the skeleton of nanocellulose fibers, and the cellulose grafted single ion conducting polymer TF-HBSC has been successfully synthesized.
[0068] 2 Characterization of morphology and physical properties
[0069] like Figure 2 As shown, Figure 2 As shown in a, due to the presence of abundant highly lithiophilic hydroxyl groups in the cellulose-grafted single-ion electrolyte TF-HBSC, the TF-HBSC artificial SEI film is in close contact with the lithium foil; Figure 2 The standard coordinate scale in a is used to estimate that the artificial SEI membrane of TF-HBSC is about 5 μm, which meets the actual application requirements of polymer artificial SEI membrane. Figure 2 In b, the S element surface scan of the TF-HBSC artificial SEI membrane shows that the S element of the 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonic acid precursor is evenly distributed on the surface of the TF-HBSC artificial SEI membrane; this confirms that the sulfonate (-SO3 - ) functional groups are evenly distributed in the cellulose-grafted single-ion electrolyte TF-HBSC, thereby promoting the uniform deposition of lithium ions on the lithium anode.
[0070] like Figure 3 As shown, Figure 3 The TEM image of a directly proves the large aggregation of sulfonic acid groups in the TF-HBSC artificial SEI film that can promote the dissociation of lithium ions, which has an obvious enlarged phase separation morphology (enlarged ion clusters). Figure 3 The difference in TEM images indicates that the brush-like TF-HBSC has a high degree of freedom of movement of sulfonate groups, which can greatly promote the aggregation of sulfonate groups dissociated from lithium ions, thereby constructing an efficient lithium ion transport channel. Figure 3 The rough morphology of the TF-HBSC membrane under the surface and 3D reconstruction in the AFM image in cd also confirms the excellent phase separation phenomenon in the TF-HBSC membrane. Therefore, due to the brush-like chemical structure of TF-HBSC, the efficient lithium ion transport channel is well constructed through the large amount of self-aggregation of highly flexible sulfonic acid groups, which lays a solid foundation for improving the ionic conductivity and lithium ion transfer number of the TF-HBSC membrane.
[0071] like Figure 4 As shown, Figure 4 The TF-HBSC membrane in a exhibits a tensile strength of 20.3 MPa and an elongation of 10.8%, which are greater than the tensile strength of 19.4 MPa and an elongation of 7.8% of the pure CNF membrane. Figure 4 The TF-HBSC membrane in b has a contact angle of only 47.0° 30 seconds after adding a drop of commercial electrolyte, showing a good electrolyte infiltration rate. The existing PP separator can obviously observe a contact angle of up to 106.3° 30 seconds after adding a drop of commercial electrolyte. This is due to the good compatibility between the large number of highly polar hydroxyl groups (derived from the CNF main chain) and sulfonate groups (derived from the grafted sulfonic acid small molecules) in the chemical structure of TF-HBSC and the organic electrolyte with high dielectric constant.
[0072] 3 Electrochemical performance characterization
[0073] like Figure 5 As shown in the figure, the electrochemical window of TF-HBSC membrane was first tested by linear sweep voltammetry (LSV). Figure 5 a shows that the TF-HBSC membrane exhibits an excellent electrochemical window of up to 4.5V, which is higher than the 4.2V value required for the commercial electrode material LiFePO4, indicating that the TF-HBSC artificial SEI membrane is fully capable of being used in batteries with lithium iron phosphate as the positive electrode system.
[0074] The symmetric cells with stainless steel gaskets were assembled using PP membrane, HBSC membrane and TF-HBSC membrane in commercial electrolyte to test their resistance values. The ionic conductivity obtained from a series of step temperature tests and the temperature were plotted as lgσ-1000 / T, and finally the obtained values were linearly fitted, as shown in Figure 5 As shown in b, the ionic conductivities of PP membrane, HBSC membrane and TF-HBSC membrane at 25 °C are 1.79×10 -4 S cm -1 , 3.80×10 -4 S cm -1 , 4.87×10 -4 S cm -1 As the temperature rises, the movement speed of lithium ions increases, and the ionic conductivity also increases. When the temperature is 85℃, the ionic conductivity of PP membrane, HBSC membrane and TF-HBSC membrane is 1.64×10 -3 S cm -1 , 2.56×10 -3 S cm -1 , 3.12×10 -3 S cm -1 The ionic conductivity of the TF-HBSC membrane / commercial electrolyte system is almost three times that of the PP membrane / commercial electrolyte system, and the ionic conductivity of the HBSC / commercial electrolyte system is slightly lower than that of the TF-HBSC / commercial electrolyte system, which indicates that F atoms are beneficial to enhancing the ionic conductivity of polymers; the enhancement of ionic conductivity is mainly attributed to the strong dissociation ability of F atoms on the high dielectric constant 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonic acid to lithium ions.
[0075] like Figure 6 As shown in the figure, in order to study the effect of lithium ion exchange and fluorination structure of TF-HBSC on the stability of lithium negative electrode, the lithium ion migration number was measured by steady-state current and AC impedance spectrum. The lithium ion migration number of TF-HBSC was calculated to be 0.64; the lithium ion migration number of HBSC was calculated to be 0.52; and the lithium ion migration number of the pure lithium negative electrode of the blank control group was 0.28. The result that the lithium ion migration number of TF-HBSC is more than twice that of the blank control group is not only attributed to the single ion conduction behavior of TF-HBSC for lithium ions, but also because SO3 anchored on the molecular skeleton of TF-HBSC - Anion pair PF6 in commercial electrolyte - Electrostatic repulsion between anions. In addition, the lithium ion migration number of TF-HBSC is slightly higher than that of HBSC, mainly due to the strong coordination interaction between the F atoms on 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonic acid with high dielectric constant and lithium ions.
[0076] 4 Stripping / deposition stability characterization
[0077] like Figure 7 As shown, Figure 7 a is a low current density of 1 mA cm -2 The results of long-term square wave constant current test under the same conditions show that the lithium symmetric battery assembled with the lithium negative electrode modified with the single-ion conductive polymer TF-HBSC responds with constant current and voltage for up to 1200h without short circuit, showing extremely small concentration polarization; this is consistent with the high lithium ion transfer number (t Li+ =0.64) is consistent.
[0078] Figure 7 b is a high current density of 10 mA cm -2 The long-term square wave constant current test results under the conditions are consistent with those at low current density, showing extremely excellent stable and long-term cycle performance. The lithium negative electrode modified with the TF-HBSC artificial SEI film exhibits the characteristics of single ion conduction, and therefore shows a higher lithium ion migration number, which in turn greatly inhibits the growth of lithium dendrites, avoids internal short circuits in the battery, and greatly improves the cycle life of lithium metal batteries.
[0079] like Figure 8 As shown in the figure, after disassembling the button cell after the constant current cycle test, the surface morphology of the lithium foil after long-term electroplating / stripping was tested by scanning electron microscopy. 8a shows that the pure lithium negative electrode before square wave cycling shows a shiny metallic luster and a smooth surface without any protrusions. 8b and 8e are the SEM surface and cross-sectional images of the pure lithium negative electrode after square wave cycling. The surface of the lithium sheet becomes very rough and dark, with many large and protruding dendrites and shows a huge volume expansion. 8c and 8f show that the lithium sheet in the lithium symmetric battery assembled with the TF-HBSC@Li negative electrode presents a smooth surface after a long-term stripping / deposition cycle of 1200h. The sharp contrast of the SEM images shows that the TF-HBSC@Li negative electrode can achieve uniform deposition of lithium ions and effectively inhibit the generation of lithium dendrites.
[0080] 5. Lithium iron phosphate battery performance characterization
[0081] like Fig. 9 As shown in Figure 2, the rate charge and discharge performance of the HBSC@Li negative electrode and TF-HBSC@Li negative electrode systems were tested in Li||LiFePO4 batteries and compared with the rate charge and discharge performance of the pure lithium negative electrode blank control system. At 25°C, the battery rate test results are shown in Figure 2. Fig. 9When TF-HBSC@Li negative electrode is used as the negative electrode of the battery, the discharge specific capacity at the rates of 0.1C, 0.2C, 0.5C, 1.0C, 2.0C, 4.0C, 6.0C, and 10.0C are 165.4 mAh g -1 , 160.3mAh g -1 , 144.9mAhg -1 , 137.1mAh g -1 , 128.8mAh g -1 , 118.3mAh g -1 , 109.2mAh g -1 , 70.5mAh g -1 , which are much higher than those of HBSC@Li negative electrode and pure lithium negative electrode. From the rate performance results of lithium iron phosphate battery, it can be seen that the high dielectric constant F atoms on TF-HBSC have a strong dissociation ability for lithium ions, which in turn improves the ionic conductivity of TF-HBSC membrane and greatly improves the rate charge and discharge performance of lithium iron phosphate battery assembled with TF-HBSC@Li negative electrode.
[0082] like Fig.10 As shown, Fig.10 a is the cycle test of three lithium anodes at room temperature 25°C with a high rate of 10C. The initial discharge capacity of TF-HBSC@Li anode is 72.5 mAh g -1 After 250 cycles of stable cycling, the discharge capacity is 59.1 mAh g -1 The capacity decay rate per cycle is relatively low (the capacity decay rate per cycle = 0.074%), which has excellent cycle stability and reversibility. In comparison, the discharge capacity of the pure lithium negative electrode has obviously decayed from 45.9 mAh g in the first cycle to 1.3 mAh g in the second cycle. -1 It dropped to 26.8 mAh g at the 125th cycle. -1 The initial discharge capacity of the HBSC@Li negative electrode is 60.7 mAh g -1 After 250 cycles, the discharge capacity is 36.0 mAh g -1 The capacity decay ratio per cycle is 0.163%. Therefore, the cycle performance of TF-HBSC@Li negative electrode is much better than that of HBSC@Li negative electrode and pure lithium negative electrode.
[0083] Fig.10 b shows the cycling test of three lithium anodes at a low temperature of -20 °C with a rate of 1C. The initial discharge capacity of the TF-HBSC@Li anode is 89.1 mAh g -1 After 1079 stable cycles, the discharge capacity is 92.1 mAh g -1, with excellent cycle stability and reversibility. The discharge specific capacity increases slightly after cycling, which is mainly attributed to the internal activation of the battery in long-term cycling at low temperatures and the thermal balance between internal heat release and environmental heat absorption.
[0084] Based on the above test data, it can be seen that TF-HBSC@Li negative electrode can function as the negative electrode of lithium metal batteries. It exhibits good electrochemical performance, lithium stripping and deposition capabilities, and long-term rate and cycle performance, which improves the low-temperature performance, cycle life and safety of lithium metal batteries.
Claims
1. A method for preparing a cellulose-based artificial SEI membrane, characterized in that: include: First, cellulose nanofiber CNF is gelated with hydrochloric acid to obtain CNF gel; then 2-bromoisobutyryl bromide BiBB is chemically grafted onto the CNF gel to obtain the precursor CNF-Br; then 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate sodium TF-HDBSNa is chemically grafted onto the precursor CNF-Br, and the resulting crude product is dialyzed to convert the sodium ions on the crude product into lithium ions to obtain a single-ion polymer TF-HBSC; finally, the single-ion polymer TF-HBSC is formed into a film to obtain a cellulose-based artificial SEI membrane.
2. The method for preparing a cellulose-based artificial SEI membrane according to claim 1, characterized in that: The preparation of CNF gel comprises: placing cellulose nanofiber CNF in water to form a CNF dispersion with a concentration of 1.0-2.0 wt%, adding hydrochloric acid at room temperature for gelation reaction for 2-8 hours, wherein the amount of hydrochloric acid used is 0.008-0.01 mmol of HCl per 1 g of CNF, to obtain CNF gel.
3. The method for preparing a cellulose-based artificial SEI membrane according to claim 1, characterized in that: The preparation of the precursor CNF-Br comprises: dispersing CNF gel in a solvent DMF, slowly dropping a DMF solution containing triethylamine and 2-bromoisobutyryl bromide under the protection of argon and an ice bath environment, stirring at room temperature for 12 to 24 hours to cause a grafting reaction, and separating, washing, and drying after the reaction is completed to obtain the precursor CNF-Br.
4. The method for preparing a cellulose-based artificial SEI membrane according to claim 3, characterized in that: The molar ratio of the precursor CNF-Br: 2-bromoisobutyryl bromide: triethylamine is 1: 2-2.4: 0.6-0.
8.
5. The method for preparing a cellulose-based artificial SEI membrane according to claim 1, characterized in that: The TF-HBSC preparation comprises: Under argon protection, CNF-Br, sodium 2,3,5,6-tetrafluoro-4-hydroxybenzenesulfonate and potassium carbonate were placed in a solvent DMSO and stirred at 120-180°C for 12-24 hours for grafting reaction. After the reaction was completed, a crude product was obtained by separation and washing. The crude product was dialyzed to convert sodium ions into lithium ions, and TF-HBSC was obtained after freeze-drying.
6. The method for preparing a cellulose-based artificial SEI membrane according to claim 5, characterized in that: The molar ratio of CNF-Br: sodium hydroxybenzenesulfonate TF-HDBSNa: potassium carbonate is 1: 0.5-0.6: 1-1.
5.
7. The method for preparing a cellulose-based artificial SEI membrane according to claim 1, characterized in that: The dialysis treatment comprises: placing the crude product in a dialysis bag and sealing it, then soaking the dialysis bag in a lithium chloride aqueous solution with a concentration of 1 to 1.5 mol / L to convert sodium ions into lithium ions, the soaking time is 24 to 36 hours, and taking out and freeze-drying after soaking to obtain TF-HBSC.
8. The method for preparing a cellulose-based artificial SEI membrane according to claim 1, wherein: The single ion polymer TF-HBSC film formation comprises: placing TF-HBSC in a solvent DMSO and stirring at room temperature for 6 to 12 hours to obtain a TF-HBSC dispersion, dripping the TF-HBSC dispersion onto a substrate surface under an argon environment, and heating at 60 to 90° C. for 4 to 12 hours to remove the solvent to obtain a transparent cellulose-based artificial SEI film.
9. A cellulose-based artificial SEI membrane, characterized in that: The cellulose-based artificial SEI membrane is prepared by any one of the methods for preparing the cellulose-based artificial SEI membrane according to claims 1 to 8.
10. A use of the cellulose-based artificial SEI membrane as claimed in claim 9, characterized in that: Used for negative electrode of lithium battery.
Citation Information
Patent Citations
Preparation method of cellulose-g-resin acid grafted copolymer
CN103145918A
Molecular brush polymer film based on cellulose network structure, and preparation method and application thereof
CN112072173A
Lithium battery negative electrode modified by artificial solid-phase electrolyte interface film as well as a preparation method and application of lithium battery negative electrode
CN113036077A
Single-ion cellulose-based gel polymer electrolyte and preparation method thereof
CN118406266A
Electrochemical Compression of Ammonia Using Ion Exchange Membranes
US20170362720A1
Cited By
Lithium metal negative electrode containing multifunctional polymer brush protective layer, preparation method of lithium metal negative electrode and lithium metal battery
CN122494584A
